Maternal child feeding knowledge and practices and growth status of young children aged 6 to 24 months in Kuala Lumpur - Chua , M. T.; Mohd Shariff , Zalilah (Nutrition Society of Malaysia, 2008)
This study was conducted to determine the association between maternal child feeding knowledge and practices with the growth status of young children. A total of 102 young children (62 boys and 40 girls) aged between 6 and 24 months old and their mothers participated in this study. A set of structured questionnaire; was used to obtain information on socio-economic, demographic characteristics, maternal feeding knowledge and practices, and anthropometric measurements of the young children. Maternal feeding knowledge was assessed in three different constructs i.e. general nutrition, breastfeeding and complementary feeding. Maternal feeding practice was assessed by examining whether mothers met the WHO guidelines for continued breastfeeding or feeding of milk or milk products, number of feeding times and number of food groups. Anthropometric measurements of the children such as weight and recumbent length were obtained using TANITA weighing scale and wooden measuring board, respectively. The anthropometric measurements were then compared to the National Center for Health Statistics (NCHS) reference. The results indicated that 18.6% (n=19) of the young children were significantly underweight, 16.7% (n=17) mildly underweight, and 3.9% (n=4) were overweight. The percentage of children with significant and mild wasting were 17.6% (n=18) and 32.4% (n=33) respectively, while 14.7% (n=15) and 34.3 (n=35) were significantly and mildly stunted respectively. Maternal feeding data showed that the mean of maternal feeding knowledge score in the three constructs were 6.73±0.18, 5.97±0.19 and 6.57±0.18, for general nutrition, breastfeeding and complementary feeding respectively. The total score for each construct was 10. The mean total knowledge score obtained was 19.26±4.12. Maternal feeding practice data indicated that 97.1% (n=99) of the mothers continued breastfeeding or feeding milk or milk products, 33.3% (n=34) of the children were fed the recommended minimum number of times, and 81.4% (n=83) of the children were fed the recommended minimum number of food groups. Statistical test on the association between maternal child feeding knowledge and practices with the growth status of young children will be further conducted. Maternal nutritional knowledge and child feeding practices should not be overlooked as factors that may influence growth status of young children.